Transcriptional Response of Burkholderia cenocepacia H111 to Severe Zinc Starvation - James Paul Barnett (Frontiers Media S.A., 2023)
Burkholderia cenocepacia is an opportunistic pathogen that is primarily associated with severe respiratory infections in people with cystic fibrosis. These bacteria have significant intrinsic resistance to antimicrobial therapy, and there is a need for more effective treatments. Bacterial zinc uptake and homeostasis systems are attractive targets for new drugs, yet our understanding of how bacteria acquire and utilise zinc remains incomplete. Here we have used RNA-sequencing and differential gene expression analysis to investigate how B. cenocepacia H111 is able to survive in zinc poor environments, such as those expected to be encountered within the host. The data shows that 201 genes are significantly differentially expressed when zinc supply is severely limited. Included in the 85 upregulated genes, are genes encoding a putative ZnuABC high affinity zinc importer, two TonB-dependent outer membrane receptors that may facilitate zinc uptake across the outer cell membrane, and a COG0523 family zinc metallochaperone. Amongst the 116 downregulated genes, are several zinc-dependent enzymes suggesting a mechanism of zinc sparring to reduce the cells demand for zinc when bioavailability is low.